Pengaruh Brand Image dan Harga terhadap Keputusan Pembelian pada Fenomena Pemboikotan Produk Unilever : Studi Kasus Konsumen Produk Lifebuoy dari Brand Unilever di Indonesia - Meilatul Maftukhah; Rizki Wahyuning Damayanti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The current phenomenon of product boycotting has caused several industrial products in Indonesia to be boycotted. Such as Lifebuoy products from the Unilever brand because they are considered to support Israeli Zionists. Unilever is a Fast Moving Consumer Goods industry that provides consumer goods with a fluctuating sales cycle. Where Lifebuoy is one of the products from this brand in the antiseptic bath soap category which has a superior Top Brand Index compared to other brands. This research is quantitative research whose calculations involve statistical numbers using the IBM SPSS Statistics 27 application.Who has a purpose to determine the influence of brand image and price on purchasing decisions for Lifebuoy products from the Unilever brand in Indonesia partially or simultaneously. Based on the results of the t test, it shows that brand image has an influence on purchasing decisions by 4.906. And the price variable has an influence on purchasing decisions by 10.374, while the results of the f test show that brand image and price variables have an influence on purchasing decisions by 328.524. And based on the research that has been conducted, it can be concluded that brand image and price influence the decision to purchase Lifebuoy products partially or simultaneously with an Adjusted R Square value of 0.725 or 72.5%.